2018
DOI: 10.1111/dom.13211
|View full text |Cite
|
Sign up to set email alerts
|

Tofogliflozin decreases body fat mass and improves peripheral insulin resistance

Abstract: The impact of tofogliflozin, a sodium‐glucose co‐transporter‐2 inhibitor, on peripheral glucose uptake in patients with type 2 diabetes mellitus (T2DM) was investigated using the hyperinsulinaemic‐euglycaemic clamp method in a single‐arm, open‐label study. The following variables were compared between before and after tofogliflozin administration for 12 weeks in 16 patients with T2DM who were receiving dipeptidyl peptidase‐4 inhibitor treatment: body weight (BW); blood pressure; glucose metabolism; liver funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 18 publications
(43 reference statements)
4
31
0
Order By: Relevance
“…Previously, SGLT2 inhibitor administration was shown to result in changes in body composition through the reduction of body fat mass ( 4 ). Thus, SGLT2 inhibitors improve not only hyperglycemia via the promotion of urinary glucose excretion, but also obesity via the promotion of lipolysis and prevention of lipogenesis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, SGLT2 inhibitor administration was shown to result in changes in body composition through the reduction of body fat mass ( 4 ). Thus, SGLT2 inhibitors improve not only hyperglycemia via the promotion of urinary glucose excretion, but also obesity via the promotion of lipolysis and prevention of lipogenesis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have shown the various beneficial effects of SGLT2 inhibitors, including reductions in the risk of cardiovascular events and mortality in diabetes mellitus ( 1 , 2 ). SGLT2 inhibitors exert glucose-lowering effects, improving insulin sensitivity through the changes in the body composition over long-term treatment ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…We repeatedly evaluated the HOMA-IR to determine changes in insulin resistance. Although insulin sensitivity should ideally be precisely evaluated using the glucose clamp procedure [26,27], this method is impractical for the long-term assessment of large numbers of patients. Nevertheless, the glucose clamp procedure is needed to accurately evaluate the ability of omarigliptin to decrease insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It also improves the function of pancreatic β cells and kidney and has beneficial effects on lipid metabolism, especially when the patient consumes the appropriate dietary carbohydrate composition (Ito et al, ). Tofogliflozin reduces body fat mass leading to improvement in insulin sensitivity and peripheral glucose uptake (Matsuba, Matsuba, Shimokawa, Nagai, & Tanaka, ). Renal function does not affect the pharmacokinetics of tofogliflozin; hence, dose adjustment is not required for T2DM patients with renal disorders (Ikeda et al, ).…”
Section: Phlorizinmentioning
confidence: 99%